1983
DOI: 10.1128/aac.24.6.835
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of tetracycline resistance determinant classes among lactose-fermenting coliforms

Abstract: Using colony hybridization techniques and DNA probes derived from four distinct tetracycline resistance determinants, we have examined the frequency of these determinants among 225 lactose-fermenting coliforms isolated from fecal samples of both humans and animals. The class B, or TnJO-type determinant, occurred most frequently at 73.3%, followed by class A (on RP1) at 21.7%, and class C (on pSC101) at 8%; 3.5% of isolates harbored two of these determinants. Hybridization to class D, carried by plasmid RA1, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
72
2

Year Published

1985
1985
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 14 publications
7
72
2
Order By: Relevance
“…This was evident from the earliest studies of the distribution of tet genes, when it was found that only 3.5% of the lactose-fermenting coliforms carried two different tet genes (169). Similar results have been found in bacteria isolated from catfish and their environment (59)(60)(61), in Shigella spp.…”
Section: Tet(a) Tet(b) Tet(c) Tet(d) Tet(e) Tet(g) Tet(h) Tet(supporting
confidence: 65%
See 1 more Smart Citation
“…This was evident from the earliest studies of the distribution of tet genes, when it was found that only 3.5% of the lactose-fermenting coliforms carried two different tet genes (169). Similar results have been found in bacteria isolated from catfish and their environment (59)(60)(61), in Shigella spp.…”
Section: Tet(a) Tet(b) Tet(c) Tet(d) Tet(e) Tet(g) Tet(h) Tet(supporting
confidence: 65%
“…and Streptomyces spp. (207) but is uncommon in facultative gramnegative bacteria, especially enteric species (8,60,61,81,115,(168)(169)(170)176). The reason for this is unknown, but a similar situation exists for the carriage of other antibiotic resistance genes (155).…”
Section: Incidence Of Tetracycline Resistancementioning
confidence: 99%
“…Molecular techniques such as PCR assays that identify the Tet resistance determinants are a valuable tool for epidemiological studies of resistance, providing important epidemiological information about the transmission of these genes through bacterial populations and the geographical and temporal spread of particular clones and allowing discrimination between clonal spread and horizontal transfer of resistance determinants (1,5,8,11,16,30). Recent studies on gram-negative bacteria have examined the distribution of specific Tet determinants using genotypic detection assays (3,5,7,11,16,21,22,27). However, only one paper (22), which included only 33 strains isolated in Mexico City, Mexico, in 1978 to 1979, has studied the distribution of these determinants in Shigella spp.…”
mentioning
confidence: 99%
“…Currently, there are 13 well-characterized tetracycline resistance determinants representing three different mechanisms of resistance. Five of these determinants, Tet A to Tet F, are found only in gram-negative bacteria (11,12,14), while Tet K, Tet L, Tet N, and Tet P have previously been described only for gram-positive species (1,4,7,23). Tet M has been found in gram-positive (3)(4)(5)(6)20), gram-negative (8,13,20,23), and cell-wall-free species (18,19), whereas Tet 0 has been associated with Streptococcus spp., Enterococcus spp.…”
mentioning
confidence: 99%